Perception of social actors about diversity policies in spanish universities - Iáñez-Domínguez, Antonio; Díaz-Jiménez, Rosa; Rodríguez-Izquierdo, Rosa M. (Convergencia Revista de Ciencias Sociales, 2021)
Diversity is increasingly a reality in higher education, linked to globalisation and the presence of unconventional students. Previous research has explored students and teachers’ perceptions about diversity in higher education. However, there is little evidence about the perception of social actors who collaborate with higher education institutions. This article explores social actors’ perceptions regarding the measures that universities implement to respond to diversity and the challenges that diversity presents to higher education institutions. Using a qualitative methodology, 18 semi-structured interviews were conducted with social actors linked to eight Spanish universities. The results indicate that their perceptions fluctuate. However, they are often linked to the groups traditionally associated with diversity: gender and disability. This shows the invisibilisation of certain groups and primarily the relationship between diversity and issues related to inequalities and equity. The conclusions discuss initiatives that could facilitate collaboration with social actors to advance the social commitment agenda in universities.